PELATIHAN DAN PENDAMPINGAN KADER KESEHATAN PEDULI ANEMIA PADA IBU HAMIL DI DESA LAJING BANGKALAN - Irawati, Deasy; Sri Wayanti; Ali Madinah (P3M Universitas Aisyiyah Surakarta, 2025)
Lajing Village in the Arosbaya Community Health Center area is recorded as a village with a fairly high incidence of anemia in pregnant women. In 2021, it was reported that out of 83 pregnant women, 17 people (20.5%). The high incidence of anemia is due to, among other things, the poor behavior of mothers in preventing anemia. To reduce the risk of anemia in pregnant women, prevention efforts are needed which are supported and carried out by all parties, including health cadres. The lack of cadres' understanding of anemia in pregnant women is a problem in providing support to pregnant women. Community Service aims to increase the participation of health cadres in early detection and prevention of anemia in pregnant women. The method used in this service is to increase cadres' knowledge about anemia. The next stage is to accompany cadres in providing education about anemia in pregnant women and being a motivator in preventing anemia in pregnant women. Based on the results of the service, it was found that there was an increase in knowledge about anemia in the cadre group. Health cadres' knowledge before receiving information was 58.3% in the poor category, after receiving information 91.7% was in the good category. Health cadres are able to provide counseling to pregnant women and are able to become caring cadres.